Izboljšanje plavalnih veščin pri otrocih z zmanjšanimi zmožnostmi v programu učenja plavanja po Halliwickovem konceptu - Groleger, Katja (Rehabilitacija (Ljubljana), 2013)
Background: The Halliwick Concept is an approach to teaching all people, but in particular those with physical and/or learning difficulties, to participate in water activities, to move independently in water, and to swim. Data on the effectiveness of Halliwick swimming programs have not been published, so we wanted to check the efficacy of our swimming program for children. We were interested in the general progress and the progress in individual skills. We also wanted to know whether the progress depends on age, the primary diagnosis of the swimmer and the frequency of exercise. Methods: In a prospective study we evaluated children who were included in a Halliwick based swimming program in the period from October 2011 to June 2012. We collected data on their gender, age, diagnosis, initial and final swimming skills tested with SWIM and the number of swimming hours during the program. Results: Ten children out of 15 in the program were evaluated with the SWIM test. They were 7.5 years old on average (range 3.3 to 14.2 years). The average SWIM test result was 40 points (SD 18) at the beginning of the program and 47 points (SD 14) at the end of the program the children progressed by 7 points on average. Those who were involved in the program for the first time improved on average for 11 points, the others for 3 points. The largest progress was achieved in the ability to enter and exit the water, longitudinal rotation, maintaining balance and transversal rotation. The frequency of exercise did not have a clear impact on the improvement of swimming skills. Conclusion: Assessment of swimming skills with the SWIM test showed that all children improved their swimming abilities, with the exception of a child with Duchene muscular dystrophy. The progress depends on the underlying disease, and partly also on the age and the frequency of exercise, but the latter would have to be studied further in a larger study.
Keywords: Child; disability; evaluation; gibalne motnje; ocenjevanje; otroci; plavanje; SWIM test; Swimming; test SWIM